Examining the impact of ai on employee’s performance and attitude in the hotel industry - Pericleous, Katerina; Liasidou, Sotiroula (My University, 2024)
In the ever-changing environment of the hospitality and tourism sectors, providing memorable guest experiences is crucial for staying ahead of the competition and cultivating client loyalty. This study examines the potential of artificial intelligence (AI) to significantly improve visitor experiences, as well as the impact on employee working experiences. The study's goal is to understand employees' emotions towards AI in terms of job performance and productivity, as well as a threatening sense of job replacement. The study distributed a self-administered questionnaire to 282 employees in 5- and 4-star hotels in Cyprus. The data collected was analysed using Structural Equation Modelling (SEM) to understand the relationships between employees' perceptions of AI, job performance, productivity, and job insecurity. In particular, the results of the study indicate employees’ insecurity of job losses when it comes to incorporating AI applications into operational processes. However, it's crucial for employees to underscore that embracing AI can boost job productivity, thereby enhancing employee and guest satisfaction. As a result, the use of AI-driven data analytics enables enterprises to gain a deeper understanding of visitor preferences and feedback, allowing for proactive service enhancements and the ability to anticipate guest requirements. Therefore, it's crucial to motivate employees to embrace AI-powered solutions, rather than feeling intimidated by them, and to comprehend that these solutions foster an environment where technology enhances human interaction and elevates the overall guest experience significantly.